Italian Immigration to Argentina 1880-1914: Assimilation or Rejection of Argentine Society? - Zaboli, Dorna (Glendon Journal of International Studies, 2015)
This paper explores the national landscape of Argentina from 1880-1914 as a means to analyze the Italian immigration experience. The central question which is posed is whether the internal factors within Argentina enabled Italian newcomers to successfully assimilate within society. A multilayered approach is utilized to examine Argentina’s immigration policy, constitution, economy, social institutions, and cultural norms. Through this analysis, it is concluded that the internal dynamics of Argentina provided Italian immigrants the capacity, resources and space to thrive which fundamentally led to their assimilation within their host country. Cette dissertation explore la composition nationale de l’Argentine des années 1880 à 1914 afin d’analyser l’expérience des immigrants italiens. La question centrale porte sur les facteurs internes de la société argentine ayant permis une assimilation réussie des Italiens nouvellement arrivés. Une approche multidimensionnelle est utilisée afin d’examiner l’immigration, la politique, la constitution, l’économie, les institutions sociales et les normes culturelles de l’Argentine. Cette analyse permet de conclure que la dynamique interne argentine a fournis aux immigrants italiens les facultés, les ressources et l’espace nécessaires à leur épanouissement, ce qui, au fond, a mené à leur assimilation à cette terre d’accueil.